Construction of a Library of Fatty Acid Esters of Hydroxy Fatty Acids - Olga G. Mountanea; Charikleia S. Batsika; Christiana Mantzourani; Christoforos G. Kokotos; George Kokotos (Molecules)
Fatty Acid Esters of Hydroxy Fatty Acids (FAHFAs) have emerged as extraordinary bioactive lipids, exhibiting diverse bioactivities, from the enhancement of insulin secretion and the optimization of blood glucose absorption to anti-inflammatory effects. The intricate nature of FAHFAs’ structure reflects a synthetic challenge that requires the strategic introduction of ester bonds along the hydroxy fatty acid chain. Our research seeks to create an effective methodology for generating varied FAHFA derivatives. Our primary approach centers on a photochemical hydroacylation reaction, merging terminal alkenes, either ω-alkenoic acids or ω-alkenyl alcohols, with commercially available aldehydes. This transformative, environmentally friendly process, orchestrated by phenylglyoxylic acid as the photoinitiator, serves as the linchpin in establishing a practical and relatively simple method for constructing a library of racemic FAHFAs. The ketones produced by the photochemical reactions are easily converted to hydroxy derivatives, which are coupled with caproic, palmitic, or oleic acid, providing a large set of FAHFAs, which broaden our ability for future structure–activity relationship studies.